A Comparison of Social Outcomes Associated with Different Fisheries Co‐Management Institutions. Issue 3 (9th August 2013) - Cinner, Joshua; Huchery, Cindy
Abstract Collaborative management (often referred to as co‐management) is increasingly being used to promote sustainability, equity, compliance, and other desirable outcomes in fisheries. However, little is known about how these outcomes are related to specific institutional arrangements (such as the types of rules in use and the forums for developing those rules). Here, we surveyed 960 resource users from 42 communities across five countries to examine how people's perceptions of livelihood and compliance outcomes are related to the: (1) number of rules in use; (2) specific configurations of rules; and (3) type of co‐management arrangement in place. We found that perceived compliance was lower when >2 rules were in use, suggesting that the complexity of regulations can hinder compliance. Additionally, we found that resource users under locally managed protected areas and customary management arrangements were more likely to perceive beneficial livelihood outcomes than users under national park and devolved governance arrangements.